1980
DOI: 10.1002/1097-0142(19800615)45:12<3018::aid-cncr2820451224>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma: Clinical-pathologic comparison of cases in postmenopausal women receiving and not receiving exogenous estrogens

Abstract: Clinical and pathologic findings were compared in 43 postmenopausal endometrial carcinoma patients who had received exogenous estrogens prior to diagnosis and 79 similar patients unexposed to estrogens. Estrogen non-users were more likely to manifest lower parity, later menopause, obesity, hypertension, and diabetes, all of which have been considered to be constitutional risk factors for the development of endometrial carcinoma. Although estrogen users and non-users had similar extent of disease as judged by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In addition, in situ estrogen metabolism, including its synthesis and degradation, has been considered recently to play a very important role in the development and progression of various human estrogen-dependent neoplasms including endometrial carcinoma especially in the postmenopausal subjects (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in situ estrogen metabolism, including its synthesis and degradation, has been considered recently to play a very important role in the development and progression of various human estrogen-dependent neoplasms including endometrial carcinoma especially in the postmenopausal subjects (2).…”
Section: Discussionmentioning
confidence: 99%
“…In situ estrogen metabolism, including its synthesis and degradation, has been considered to play a very important role in the development and/or progression of various human estrogen-dependent neoplasms including endometrial carcinoma (2). In endometrial carcinoma, in situ 17␤-estradiol availability has been demonstrated to be closely related to the pathogenesis and development of endometrial proliferative disorders including endometrial hyperplasia and carcinoma, especially of the endometrioid type (3).…”
Section: Introductionmentioning
confidence: 99%
“…Forty-six normal cycling human endometria (26 proliferative phase, 20 secretory phase), 36 endometrial hyperplasias 3 To whom correspondence should be addressed. E-mail: s221t@mail.tains.tohoku.ac.jp (16 simple hyperplasia, nine complex hyperplasia, and 11 atypical complex hyperplasia), and 103 endometrial endometrioid adenocarcinomas (49 well differentiated, 32 moderately differentiated, 22 poorly differentiated; 67 stage I, 12 stage II, 21 stage III, four stage IV) were retrieved from the surgical pathology files of Tohoku University Hospital, Sendai, Japan.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…(3,4) In endometrial carcinoma, in situ 17β-estradiol (E2) availability has been reported to be closely associated with the pathogenesis and development of endometrial proliferative disorders including endometrial hyperplasia and carcinoma, especially the endometrioid type.…”
mentioning
confidence: 99%
See 1 more Smart Citation